Antisipasi Keterlibatasan Siswa dalam Geng Motor melalui Perencanaan Program Rohis - Hasibuan, M Mufri Azwar; Nurhanifah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to analyze the program planning implemented by the Islamic Spiritual Organization (Rohis) of SMA Dharmawangsa in anticipating student involvement in motorcycle gangs. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that the Rohis program planning includes activities focused on spiritual development, strengthening religious character, and increasing student participation in positive religious activities. However, the implementation faces challenges such as low student interest and limited support from the school administration. Despite these obstacles, the program has proven to be quite effective in fostering discipline and reducing deviant behavior among students. This study recommends stronger collaboration between Rohis, guidance and counseling teachers, and school security authorities to enhance preventive strategies and broaden the reach of student development initiatives.